1993
DOI: 10.1128/aac.37.6.1313
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of rifampin by Nocardia brasiliensis

Abstract: Rifampin was glycosylated by a pathogenic species of Nocardia, i.e., Nocardia brasiliensis. The structures of two glycosylated compounds (RIP-1 and RIP-2) isolated from the culture broth of the bacterium were Rifamycins are members of the naphthalenic ansamycin group of antibiotics characterized by a 17-membered ansa chain (1,5,11,17 (Becton Dickinson, Cockeysville, Md.). One loopful of spores or mycelial fragments from the slant cultures of Nocardia spp. was inoculated into a 10-ml Erlenmeyer shake flask con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 21 publications
1
55
0
Order By: Relevance
“…At least four RIF-deactivating enzymes have been described: ADP-ribosyltransferase (Arr) (6), glycosyltransferase (Rgt) (7,8), phosphotransferase (Rph) (8 -11), and RIF monooxygenase (12, 13). Arr and Rgt act on a critical hydroxyl group (C23) located on the ansa aliphatic chain of RIF, whereas Rph adds a phosphate group to the C21 hydroxyl.…”
Section: Rifampicin (Rif)mentioning
confidence: 99%
See 2 more Smart Citations
“…At least four RIF-deactivating enzymes have been described: ADP-ribosyltransferase (Arr) (6), glycosyltransferase (Rgt) (7,8), phosphotransferase (Rph) (8 -11), and RIF monooxygenase (12, 13). Arr and Rgt act on a critical hydroxyl group (C23) located on the ansa aliphatic chain of RIF, whereas Rph adds a phosphate group to the C21 hydroxyl.…”
Section: Rifampicin (Rif)mentioning
confidence: 99%
“…Covalent modification of RIF hydroxyls with ADP-ribose or phosphate results in high level resistance in Escherichia coli, such as a 64-fold increase in the RIF minimal inhibition concentration (6,10). Modification of RIF by Rgt results in a 4-fold increase of Streptomyces speibonae cultures (7) and markedly reduces the activity against Gram-positive bacteria (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 As to rifampicin (RIF), the rpoB2 gene, a duplicated copy of the RNA polymerase b-subunit gene containing RIF-resistant amino acid substitutions, has been predicted to be a resistance determinant and its contribution to the RIF resistance of N. farcinica has been demonstrated experimentally. 2 On the other hand, decolorization of RIF by N. farcinica has been reported 3,4 and the sequenced strain IFM 10152 decolorizes RIF in prolonged culture (unpublished observation). This observation implies the participation of decolorization in RIF resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that this inactivation is a species-specific phenomenon in this bacterium [6]. We also reported unique inactivation mechanisms of pathogenic Nocardia against clinically useful antibiotics such as rifampicin and erythromycin [7,8]. The present biotransformation of sterol-type compounds is commonly observed in pathogenic Nocardia species (data not shown), but our preliminary study indicates that other Nocardia species have a different transformation mechanism against bile acids (1, 2 and 3).…”
Section: Structure Elucidationmentioning
confidence: 82%